DOI: 10.12681/eadd/16147
|View full text |Cite
|
Sign up to set email alerts
|

Very low frequency EM wave studies of transient luminous events in the lower ionosphere

Abstract: First of all, I would like to express my gratitude to my supervisor, Christos Haldoupis, for his guidance with my thesis work during my three and a half years at the University of Crete. We shared many hours of stimulating discussions which have also provided me with new ways of looking at scientific problems. I am also very thankful for his hospitality and kindness which made my stay on Crete even more enjoyable. I thank to the Physics Department of the University of Crete and my professors for the graduate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 111 publications
1
8
0
Order By: Relevance
“…The sprite related VLF waves had long recovery times (~ 30 -300 s), which suggests spatially extended and diffuse regions of electron density increases at altitudes higher than 75 km. This agrees with the theoretical prediction of air breakdown in the upper D-region during sprite occurrence triggered by strong quasi-static electric fields Mika (2007). has discussed experimental data in which the incident VLF transmitter signal seems to be scattered from horizontally extended diffuse regions of electron density enhancements, most likely associated with halos or diffuse regions of the upper part of carrot sprites, rather than small scale streamers observed at lower altitudes.…”
supporting
confidence: 88%
“…The sprite related VLF waves had long recovery times (~ 30 -300 s), which suggests spatially extended and diffuse regions of electron density increases at altitudes higher than 75 km. This agrees with the theoretical prediction of air breakdown in the upper D-region during sprite occurrence triggered by strong quasi-static electric fields Mika (2007). has discussed experimental data in which the incident VLF transmitter signal seems to be scattered from horizontally extended diffuse regions of electron density enhancements, most likely associated with halos or diffuse regions of the upper part of carrot sprites, rather than small scale streamers observed at lower altitudes.…”
supporting
confidence: 88%
“…Good agreement with the observed recovery times of 20 to 250 s was obtained assuming electron density increases at altitudes of 75 to 85 km by factors from 10 2 to 10 4 times the unperturbed densities. This, in addition to the strong forward scattering pattern observed in relation to the VLF events recorded on Crete, leads to the conclusion that the incident VLF transmitter signals underwent scattering from horizontally extended diffuse regions of electron density enhancements, most likely associated with halos or the diffuse region of the upper part of carrot sprites, rather than small-scale streamers observed at lower altitudes (Mika 2007).…”
Section: Perturbations By Spritesmentioning
confidence: 85%
“…Haldoupis et al (2006) reported a new category of early VLF, namely "early/slow" events having the longer onset duration, of < 100 ms to couples of seconds, with similar signatures of recovery. Mika (2007) have done the detailed work on these events. Mika and Haldoupis (2008) from EuroSprite-2003 campaign data show that there is one-to-one correlation between sprite and early/fast events.…”
Section: Introductionmentioning
confidence: 99%